Survey of arthropod assemblages responding to live yeasts in an organic apple orchard - Andreadis, Stefanos S.; Witzgall, Peter; Becher, Paul G. (Frontiers in Ecology and Evolution, 2015)
Associations between yeasts and insect herbivores are widespread, and these inter-kingdom interactions play a crucial role in yeast and insect ecology and evolution. We report a survey of insect attraction to live yeast from a community ecology perspective. In the summer of 2013 we screened live yeast cultures of Metschnikowia pulcherrima, M. andauensis, M. hawaiiensis, M. lopburiensis, and Cryptococcus tephrensis in an organic apple orchard. More than 3,000 arthropods from 3 classes, 15 orders, and 93 species were trapped; ca. 79% of the trapped specimens were dipterans, of which 43% were hoverflies (Syrphidae), followed by Sarcophagidae, Phoridae, Lauxaniidae, Cecidomyidae, Drosophilidae, and Chironomidae. Traps baited with M. pulcherrima, M. andauensis, and C. tephrensis captured typically 2.4 times more specimens than control traps; traps baited with M. pulcherrima, M. hawaiiensis, M. andauensis, M. lopburiensis and C. tephrensis were more species-rich than unbaited control traps. We conclude that traps baited with live yeasts of the genera Metschnikowia and Cryprococcus are effective attractants and therefore of potential value for pest control. Yeast-based monitoring or attract-and-kill techniques could target pest insects or enhance the assemblage of beneficial insects. Manipulation of insect behavior through live yeast cultures should be further explored for the development of novel plant protection techniques.